Dual Inhibitors Targeting DNA and Histone Deacetylases - Chen Chen; Xinying Yang; Xuben Hou; Hao Fang (Georg Thieme Verlag KG, 2020)
Histone deacetylases (HDACs) regulate the acetylation status of histones and structural status of chromatin. The chromatin structure becomes relaxed after inhibition of HDAC, leading to DNA exposed to DNA disrupting agents, and eventually causing DNA dysfunction. Recently, more and more dual inhibitors targeting DNA and HDACs have been reported to be applied to cancer treatment. In this review, we describe the current status of dual inhibitors targeting DNA and HDACs, summarize their pharmacological characters, and predict their further trend in the field.